Phenotypic and genotypic characterization of listeria monocytogenes isolated from wet market in Kuching, Sarawak - Hafizah, Booty. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Infonnation on the phenotypic and genotypic characterization of Listeria monocytogenes isolated from food and environment is very limited in Sarawak. Therefore, the present study was undertaken to investigate the occurrence and characterization of L. monocytogenes in food from wet market in Kuching, Sarawak. A total of 308 foods and counter top swab samples were collected from September to December 2005. The identification of the bacterial species was based on a morphological appearance on a chromogenic medium called CHROMagar Listeria agar, biochemical test, followed by specific PCR. Using a pair of primer to amplify a product of 730 bp in size, 53 L. monocytogenes isolates were successfully confinned. All the 53 isolates were tested using the antibiotic susceptibility test and were found to be resistant toward nalidixic acid and moderate to highly resistance to streptomycin, vancomycin, gentamycin, chloramphenicol, erythromycin and tetracycline. All the 53 isolates were, however susceptible to ampicillin and this finding revealed that the ampicillin is a suitable drug for the treatment of listeriosis. Overall, this study has recorded the occurrence and distribution of L. monocytogenes in food from wet market in Kuching, Sarawak. The study has also generated preliminary infonnation that suggests plasmidless strain of L. monocytogenes express resistance to antibiotic and that these resistant gene may be encoded in the bacterial chromosomal DNA itself.